Paddling her own canoe : the times and texts of E. Pauline Johnson (Tekahionwake) - Strong-Boag, Veronica Jane (Studies in gender and history, 2000)
The only major scholarly study that examines E. Pauline Johnson's diverse roles as a First Nations champion, New Woman, serious writer and performer, and Canadian nationalist.